Mechanical, thermal and acoustic behaviour of polymer-based composite materials produced with rice husk and expanded cork by-products. (10th April 2020) - Marques, Beatriz; Tadeu, António; António, Julieta; Almeida, João; de Brito, Jorge
Highlights: Development of innovative composites with rice husk and expanded cork granules. Increasing the board's density and cork content improves the mechanical performance. The effect of density on water vapour and water absorption properties was notable. The use of rice husk can improve the impact and sound absorption performance. Multi-criteria analysis was used to select formulations for wall and floor uses. Abstract: In this work, innovative polymer-based composite materials made with rice husk and expanded cork by-products have been produced and characterised. First, rice husks and expanded cork granules were studied separately to ascertain material properties, such as thermal conductivity, water vapour resistance, thermal stability and specific heat capacity. After that, different composite mixes were formulated and the resulting boards evaluated in terms of their mechanical, hygrothermal and acoustic properties. The influence of the different mix ratios and composite densities on the overall performance is also discussed. The experimental results indicate that higher contents of rice husk can contribute to improve the acoustic performance, while the incorporation of expanded cork granules in the composite formulations helps to reduce the thermal conductivity and improve the mechanical behaviour. The applicability of these composites in constructive systems such as walls and floors was assessed. For this purpose, the most suitable composite formulations were selected after a multi-criteria analysis was performed. The static and dynamic thermal performance provided by building solutions that included the selected composite materials was then evaluated. The results suggest that construction solutions based on these composite materials can be used in buildings, thereby contributing to reduce energy consumption during buildings' service life.